A Unique Presentation of Cutaneous Diffuse Large B-Cell Lymphoma. (7th April 2020) - Awad, Mary; Holzwanger, Erik; Jubbal, Sandeep
Abstract : Cutaneous B-cell lymphomas (CBCL) are rare heterogeneous neoplastic diseases composing about 22.5% of all cutaneous lymphomas. These diseases can be divided into primary and secondary cutaneous variants with primary cutaneous B-cell lymphoma (PCBCL) divided into three distinct entities including primary cutaneous marginal zone lymphoma, primary cutaneous follicle center lymphoma, and primary cutaneous diffuse large B-cell lymphoma, leg type (PCDLBCL, LT). Secondary cutaneous diffuse large B-cell lymphoma (CDLBCL) and PCDLBCL, LT are more aggressive neoplasms compared to the aforementioned CBCL with survival rates of 37% and 50% after 5 years, respectively. CDLBCL can present as cutaneous or subcutaneous nodules, papular lesions, or indurated plaques. Here, we present a case of CDLBCL of an 88-year-old female that was mistaken for lower extremity cellulitis with phlegmon. Our patient failed two courses of antibiotic therapy as an outpatient and received a third as an inpatient before a cutaneous biopsy clinched the diagnosis.